Intertemporal Price Discrimination - Stokey, Nancy L. (Quarterly Journal of Economics, 1979)
I. Introduction, 355.—II. No production costs: "pure" discrimination, 357.—III. Positive production costs, 363.—IV. Conclusion, 367.